(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
This study aims to analyze the regulatory framework for combating mafia infiltration from a labor law perspective. Specifically, it seeks to highlight intersections and conflicts between certain labor law institutions and the relevant regulations, as well as their impact on the workforce. To this end, three measures will be examined: anti-mafia documentation, the Quality Agricultural Work Network, and subcontracting. The analysis reveals a paradox between the progressive liberalization of market regulation and the reliance on (merely) repressive responses, which are poorly aligned with labor law provisions. The study proposes a reading of anti-mafia regulations that better balances the diverse interests at stake.